The Relationship between LBW and Exclusive Breastfeeding with the Incidence of Stunting in Toddlers in 2021 - Marowiyah, Siti; Rusmilawaty, Rusmilawaty; Suhrawardi, Suhrawardi; Rafidah, Rafidah (JURNAL KEBIDANAN BESTARI, 2023)
Stunting is a chronic condition that describes stunted growth due to malnutrition over a long period of time. As many as 1.3 million Indonesian children are stunted and Indonesia is the third country with the highest prevalence of stunting in the Southeast Asia/South-East Asia Regional (SEAR) region. The purpose of this study was to determine the relationship between LBW and exclusive breastfeeding with the incidence of stunting in toddlers. The research method used the Literature Study method taken from 7 journals consisting of 4 national journals and 3 international journals. Data analysis in this study is descriptive analysis. The results of the study based on the literature review of 7 journals, the lowest percentage of LBW incidence was found to be 7.8% and the highest percentage was 34.1%. Exclusive breastfeeding was found to have the lowest percentage of 26.7% and the highest percentage of 85%. The lowest percentage of stunting incidence was found to be 17%, and the highest percentage was 50%. 7 research journals that used all stated that there was an association between LBW and the incidence of stunting in toddlers. 4 research journals that use all state that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers.